Incidencia de enfermedades hemoparasitarias mediante la técnica de Diff Quick en predios de equinos (Equus caballus) en el cantón Baba Provincia de Los Ríos - Zambrano León, Evelyn Escarleth (2023)
Hemoparasitic diseases represent a great problem worldwide, not only in animal health but also in public health, among the main diseases that affect the horse we have piroplasmosis, anaplasmosis and trypanosomiasis, this is becoming one of the conditions every day. most worrisome for the cattle producer. Due to the aforementioned, the present work was carried out with the purpose of determining the incidence of hemoparasitic diseases in horses of the canton Baba Province of Los Ríos. Therefore, in this investigation, 278 equines were sampled, which were distributed in 33 farms belonging to the Baba canton, Los Ríos province, among them there are 109 horses, 59 foals, 48 fillies and 62 mares. Therefore, the data was evaluated using the Percentage Method to determine the percentage of how many cases are positive or negative to hemoparasites in horses. Positive cases were evaluated using the Non-Parametric Test for a single sample, Chi Square Test. 12 were positive (4%) and 266 negative (96%). 5 cases of Ehrlichia (41.66%) and 5 ehrlichia platys (41.66%) and 2 theileria equis (16.66%) were found. In the distribution by sex it is said that there are 38% females and 62% males. Among the animals most susceptible to hemoparasitic diseases are horses.